The three vectors
,
, and
each terminate on the plane. We can get two vectors that lie on the plane itself (or rather, point in the same direction as vectors that do lie on the plane) by taking the vector difference of any two of these. For instance,
![\langle1,0,8\rangle-\langle0,0,1\rangle=\langle1,0,7\rangle](https://tex.z-dn.net/?f=%5Clangle1%2C0%2C8%5Crangle-%5Clangle0%2C0%2C1%5Crangle%3D%5Clangle1%2C0%2C7%5Crangle)
![\langle0,1,9\rangle-\langle0,0,1\rangle=\langle0,1,8\rangle](https://tex.z-dn.net/?f=%5Clangle0%2C1%2C9%5Crangle-%5Clangle0%2C0%2C1%5Crangle%3D%5Clangle0%2C1%2C8%5Crangle)
Then the cross product of these two results is normal to the plane:
![\langle1,0,7\rangle\times\langle0,1,8\rangle=\langle-7,-8,1\rangle](https://tex.z-dn.net/?f=%5Clangle1%2C0%2C7%5Crangle%5Ctimes%5Clangle0%2C1%2C8%5Crangle%3D%5Clangle-7%2C-8%2C1%5Crangle)
Let
be a point on the plane. Then the vector connecting
to a known point on the plane, say (0, 0, 1), is orthogonal to the normal vector above, so that
![\langle-7,-8,1\rangle\cdot(\langle x,y,z\rangle-\langle0,0,1\rangle)=0](https://tex.z-dn.net/?f=%5Clangle-7%2C-8%2C1%5Crangle%5Ccdot%28%5Clangle%20x%2Cy%2Cz%5Crangle-%5Clangle0%2C0%2C1%5Crangle%29%3D0)
which reduces to the equation of the plane,
![-7x-8y+z-1=0\implies z=7x+8y+1](https://tex.z-dn.net/?f=-7x-8y%2Bz-1%3D0%5Cimplies%20z%3D7x%2B8y%2B1)
Let
. Then the volume of the region above
and below the plane is
![\displaystyle\int_0^1\int_0^1(7x+8y+1)\,\mathrm dx\,\mathrm dy=\boxed{\frac{17}2}](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Cint_0%5E1%5Cint_0%5E1%287x%2B8y%2B1%29%5C%2C%5Cmathrm%20dx%5C%2C%5Cmathrm%20dy%3D%5Cboxed%7B%5Cfrac%7B17%7D2%7D)
The answer for this is 37.5. I can't show the work because i searched it up on Google.
1. your leading coefficient has to be 1 (nothing before the x^2). If there is you have to divide that out before you start.
2. Move your constant (the number without any x attached) to the other side of the equation
3. take 1/2 of the b term (the one with the x attached) and then square it and then add it to both sides
4. Factor the left side
5. Set each factor equal to 0 and solve
Here is an example:
4x^2-24x+20=0
The first term is not a 1 so we have to divide it out by 4 first
x^2-6x+5=0
Move the 5 to the other side. It becomes negative.
x^2-6x=-5
Take 1/2 of 6 (3) then square it (9) and add it to both sides.
x^2-6x+9=-5+9
Factor the left side
(x-3)(x-3)=4
(x-3)^2=4
To solve you need to square root both sides
x-3=+/-
x-3=+/-2
x=3+2=5
x=3-2=1
Those would be your two answers.
<span>Hope that helps</span>
Answer:
Jaffrey will end up making $1214 in the first year
Step-by-step explanation:
950 + 12(22) = ?
first lets find out what 12 * 22 =?
12 * 22 = 264
now lets add 264 to 950
264 + 950 = 1214
The median is 48 because it is the biggest number and the biggest number is the median